Effects of hard red winter wheat particle size in meal diets on finishing pig growth performance, diet digestibility, and caloric efficiency - De Jong, Jon A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C.; Paulk, Chad B.; Jones, Cassandra K.; Stark, Charles R.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 288 pigs (PIC 327 × 1050; initially 96.4 lb) were used in an 83-d study to determine the effects of hard red winter wheat particle size on finishing pig growth performance, diet digestibility, and caloric efficiency. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 3 treatments with 8 pigs per pen and 12 pens per treatment. The same wheat-soybean meal–based diets were used for all treatments. Diets were fed in three phases in meal form. The 3 dietary treatments were hard red winter wheat ground with a hammer mill to 730, 580, or 330 μ. From d 0 to 40, decreasing wheat particle size decreased (linear; P < 0.05) ADFI but improved (quadratic; P < 0.05) F/G and caloric efficiency (CE), with no change in ADG. From d 40 to 83, decreasing wheat particle size increased (quadratic; P < 0.05) ADG and improved (linear; P < 0.05) F/G and CE, with no change in ADFI. Overall from d 0 to 83, decreasing wheat particle size improved (linear; P < 0.05) F/G and CE on both an ME and NE basis, with no difference in ADG or ADFI. Finally, reducing wheat particle size improved (linear; P < 0.05) DM and GE digestibility. In summary, fine-grinding hard red winter wheat was detrimental to feed intake in early finishing, but improved ADG in late finishing and improved F/G in both periods and overall. Dry matter and GE digestibility as well as CE were all improved for the overall period with fine-grinding wheat. Grinding wheat from 730 to 330 improved the caloric content on an NE basis by 100 kcal/lb.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Finishing pig; Performance; Particle size; Wheat